First fossil Calopterygoidea (Odonata: Zygoptera) from Southeastern Asia: A new genus and species from the Paleogene of China - Lin, Qi-bin (2010)
Sinocalopteryx shangyongensis nov. gen., nov. sp., the first fossil calopterygoid from eastern Asia, is described from the earliest Eocene of Southwest China. Although the new genus has the principle synapomorphies of Calopterygoidea, it possesses a unique structure (possible reversal) in the pattern of vein RP1/2.